Strengthening Gross Motor Skill of Children with Intellectual Disability Using Circuit Training - Desi Chuluqi Fitri; Sopingi Sopingi; Sihkabuden Sihkabuden (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2018)
The aim of this research is to identify the effect of Circuit Training towards gross motor skills on children with moderate intellectual disability in SDLBN Kedungkandang Malang. The research implements Single Subject Research design type A-B-A. The subject of this research is children with moderate intellectual disability, and data collection is conducted for 18 sessions. The results of the research show that there is an effect in the use of Circuit Training on gross motor skill of children with intellectual disability with an overlap close to 0%. It is concluded that Circuit Training affects gross motor skills on children with intellectual disability.